The golden dawn's "nationalist solution": explaining the rise of the far right in Greece - Vasilopoulou, Sofia (Palgrave pivot, 2015)
"What explains the dramatic rise of the extreme, ultranationalist Golden Dawn in a country that has experienced Nazi invasion and a military dictatorship? This book places the rise of the Golden Dawn in the context of the Eurozone crisis and argues that its rise is not merely the product of economic malaise. Rather, the success of the Golden Dawn is dependent on the extent to which it was able to propound plausible solutions to the three sets of crises--economic, political and ideological--that culminated in an overall crisis of the nation-state and democracy in Greece. Within this context, the authors examine the Golden Dawn's strategic response to the crisis in terms of the offering of a "nationalist solution" through the employment of the twin fascist myths of social decadence and national rebirth in its discourse. It is through these two myths that the Golden Dawn promises the disillusioned an escape from their social, economic and overall human desolation"--